Teenagers’ “Gender Trouble” and Trickster Aesthetics in Gina Moxley’s Danti Dan - Kurdi, Mária (ABEI Journal, 2002)
Recently a type of drama has emerged in Ireland with characters representing isolated social groups that were overlooked or considered as marginal. It includes plays with teenagers as protagonists, conceived by writers who seem to be inspired by the realization that the treatment of, and possibilities for children and youth are indicators of a society’s moral health. Christina Reid’s Joyriders (1986), Brownbread (1986) by Roddy Doyle, and Enda Walsh’s DiscoPigs (1996) are a few notable examples. Danti Dan, Gina Moxley’s 1995 play is set in rural Ireland during the summer of 1970, with the parents not yet conscious of the fact that their children respond to a rapidly changing world and its sexual challenges in ways very different from the traditional patterns.The present paper applies the trickster aesthetics as its main theoretical position, to create a discursive space for the investigation of a set of issues surrounding and underpinning the central concern of the play, the “gender trouble” of teenagers in the particular Irish context which has a still largely patriarchal structure. As a parallel, the analysis relies on the trickster signification in Toni Morrison’s novel Sula (1973), deploys the feminist psychology of Nancy Chodorow, and draws from Teresa Lauretis’s discussion of gender representation in “Technologies of Gender.”